Coupling of NMDA receptors and TRPM4 guides discovery of unconventional neuroprotectants - Yan, Jing; Bengtson, C. Peter; Buchthal, Bettina; Hertle, Anna M.; Bading, Hilmar (Science, 2020)
Excitotoxicity induced by NMDA receptors (NMDARs) is thought to be intimately linked to high intracellular calcium load. Unexpectedly, NMDAR-mediated toxicity can be eliminated without affecting NMDAR-induced calcium signals. Instead, excitotoxicity requires physical coupling of NMDARs to TRPM4. This interaction is mediated by intracellular domains located in the near-membrane portions of the receptors. Structure-based computational drug screening using the interaction interface of TRPM4 in complex with NMDARs identified small molecules that spare NMDAR-induced calcium signaling but disrupt the NMDAR/TRPM4 complex. These interaction interface inhibitors strongly reduce NMDA-triggered toxicity and mitochondrial dysfunction, abolish cyclic adenosine monophosphate–responsive element–binding protein (CREB) shutoff, boost gene induction, and reduce neuronal loss in mouse models of stroke and retinal degeneration. Recombinant or small-molecule NMDAR/TRPM4 interface inhibitors may mitigate currently untreatable human neurodegenerative diseases.